Indonesia Merger Control Re-Evaluation : Twenty Years' Experience In Legal Limbo - Setyawati, Ria; Iman Prihandono; Kagramanto, Lucianus Budi; Stefan Koos (Universitas Airlangga, 2024)
This paper not only discusses the issue of the approach used, the issue of ex-post and ex-ante merger control regulation usage, issues of conflict of norms, overlapping legal rules, and the existence of legal vacuum which complicates the enforcement of rules regarding merger control in Indonesia. The legal issues examined in this paper concern the characteristics of merger control based on the ratio decidendi of KPPU decisions during the 20 years of enforcing business competition law in Indonesia and the ius constituendum of the ex-ante and ex-post approach. This research is based on normative legal research using a statute approach, conceptual approach, case approach, and comparative approach method. These methods lead to the conclusion of the research, which is, that in the past 20 years, Indonesia has experienced a change in the ex-post merger control approach, resulting in partiality in the articles applied that are not entirely used in KPPU decisions. Furthermore, the idealized rules (ius constituendum) on the control of mergers in Indonesia, outlined in Law No. 5 of 1999, will be examined based on the principles and objectives of competition law enforcement in the country.